Bacterial Characteristics of Intestinal Tissues From Patients With Crohn’s Disease - Sun, Desen; Ge, Xiaolong; Tang, Shasha; Liu, Yaxin; Sun, Jun; Zhou, Yuping; Luo, Liang; Xu, Zhengping; Zhou, Wei; Sheng, Jinghao (Frontiers in Cellular and Infection Microbiology, 2021)
Background and aims: It is believed that intestinal bacteria play an indispensable role in promoting intestinal inflammation. However, the characteristics of these tissue-associated bacteria remain elusive. The aim of this study is to explore the bacterial loads, compositions, and structures in the non-inflamed mucosa, inflamed mucosa, and creeping fat taken from Crohn’s disease (CD) patients. Methods: Non-inflamed mucosa, inflamed mucosa, and creeping fat samples were obtained from 10 surgical patients suffering from CD. Total bacterial DNA was extracted in a sterile environment using aseptic techniques. The V3-V4 regions of bacterial 16S rDNA were amplified and analysed using standard microbiological methods. qPCR was used to confirm the change in abundance of specific species in additional 30 independent samples. Results: Inflamed mucosa exhibited the highest bacterial load (3.8 and 12 times more than that of non-inflamed mucosa and creeping fat) and species diversity. The relative abundance of Proteobacteria was dominant in most samples and was negatively associated with Firmicutes. Moreover, the relative abundances of Methylobacterium and Leifsonia in creeping fat significantly increased more than twice as much as other tissue types. The bacterial community structure analysis showed that the bacterial samples from the same individual clustered more closely. Conclusion: This study reveals the significant differences in bacterial load, species diversity, and composition among different intestinal tissue types of CD patients; and confirms that the bacterial samples from the same individual are highly correlated. Our findings will shed light on fully revealing the characteristics of tissue-associated bacteria and their roles in CD pathogenesis.